G342 Health equity audit of provision of specialist paediatric neurorehabilitation services in england. (May 2019) - Kallfa, N; Lumsden, D; Williams, J; Sharples, PM
Abstract : Background: Intensive early neurorehabilitation is required after severe Acquired Brain Injury (ABI), usually necessitating in-patient care. Adult in-patient Specialist Neurorehabilitation services have been commissioned by NHS England since 2013, but there is no consistent provision and standard for specialist neurorehabilitation services for children. Aims: To survey arrangements for ABI children requiring in-patient neurorehabilitation across England. Methods: A questionnaire was sent to Lead Clinicians at all paediatric Regional Neuroscience Centres (RNSC) and two stand-alone specialist neurorehabilitation units in England. Centres were asked about neurorehabilitation clinical practice and demographic details of in-patients treated 2012–2015. Results: 17 centres responded, 15 RNSC, 2 stand-alone units. Only 29% had neurorehabilitation funding arrangements separate to acute neurology/neurosurgery tariffs. Only 10% had ring-fenced neurorehabilitation beds. Total patients receiving in-patient neurorehabilitation were estimated at 1589 over 3 years (mean/year=530). Numbers increased over time (464 (2012/13); 530 (2013/14); 595 (2014/15)). Estimated mean number of patients treated per centre/year=40 (range 2–98). 18% of centres accepted external neurorehabilitation referrals, 82% did not. 47% had a process for care transfer from ?A3B2 re 3, j?>acute services to neurorehabilitation, 53% did not. Proportion of total neurorehabilitation in-patients classed as severe ranged from 25%–90%. 6% of centres reported having >7 neurorehabilitation in-patients at any time; 41% 2–7; 41%<2. Length of neurorehabilitation stay ranged from 7–375 days. Percentage of cases with distance from centre to home > 45 min by road ranged from 3%–100%. Many centres reported staffing deficiencies; 40% had protected time for multi-disciplinary team (MDT) meetings for all members, 20% for some, 40% for none. 86% of MDTs included non-NHS funded members. Most patients were discharged from RNSCs to home, but some were discharged as in-patients to district hospitals or specialist neurorehabilitation unit. Conclusions: Considerable neurorehabilitation in-patient activity is taking place in RNSCs, despite general absence of secure funding or dedicated beds. Inter-centre variations in funding, clinical practice and discharge destinations indicate absence of clear and consistent pathways for children with ABI and other conditions requiring neurorehabilitation. Care is inequitable across England and compared to adults. Neurorehabilitation is an integral part of the neuroscience clinical pathway and should be commissioned as a specialist service.